Optimized Frame Design for Head Loss Testing Equipment Through Material Strength Analysis - Hendrikus Wermasaubun; Muhamad Fitri; Abdul Hamid; Dedik Romahadi (Universitas Mercu Buana, 2024)
This article presents the design and analysis of a frame for head loss testing equipment, crucial for evaluating flow losses in pipe installations. The objective was to develop a robust yet lightweight frame that could withstand the operational loads imposed by the testing equipment. The frame, which supports essential components such as pipes, venturi meters, elbows, and reducers, was constructed using ASTM A500 hollow sections with dimensions of 20 x 20 x 1.6 mm and 35 x 35 x 1.6 mm. These dimensions were selected for their balance between strength and weight, validated through strength analysis and SolidWorks simulations. Conducted at Universitas Mercu Buana, the project involved the design, manufacturing, and testing of the frame to determine its load-bearing capacity. The results from the SolidWorks simulations confirmed the frame's structural integrity, which was further validated by its successful application in a practical setup. This study demonstrates the effectiveness of a systematic design approach, integrating material selection, load analysis, and simulation to achieve an optimal solution. The findings contribute valuable insights into the use of ASTM A500 hollow sections in structural applications, particularly where both strength and weight are critical. This work sets a precedent for future designs in mechanical engineering, offering a reliable framework for developing durable and efficient testing equipment.